(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Excessive anthropic occupation reduces the coastal extension and causes significant impacts on the ecosystem. Urban evolution in coastal areas has reached a point of no return. For this reason, the knowledge about whether a particular type of infrastructure or vegetation on a frontal dune could cause greater or lesser impact on the beach is extremely useful for urban planning. The study area was Pehuen Co (Fig. 1), a town located in the southwest of the Buenos Aires Province (Argentina). The aim of this work is to analyze the evolution of beach profiles backed with different foredune cover in order to understand the erosion/accretion processes that may be related to the various dynamic conditions. This will provide useful information to decision makers for urban planning and sustainable management projects orientated for short, medium and long terms. Pehuen Co is a dissipative beach with eastwest coastal orientation within a region with alternating wet and dry periods. Normally, rains are concentrated in springsummer, decreasing in autumn and beco ming minimal in winter. The prevailing winds are from N and NW, with greater intensity in the spring and summer, mainly December and January. The study area coincides with the smaller beach of the downtown sector (Fig. 2). To the west, the foredune has been heavily eroded and has a steep front, whereas to the east there are vegetated, large dunes. The dominant vegetation is Tamarix gallica and Carpobrotus edulis, which are not observed in the walkways to the beach or where there are infrastructures over the foredunes. Beach profiles in different geomorphological situations were analyzed in order to describe their behavior. Three different sectors separated 50 m from each other were selected: ZC1 next to a restau rant on top of the frontal dune, ZC2 on the vegetated dune, and ZC3 on a walkway to the beach (Fig. 2). Monthly beach profiles were carried out from July 2007 to June 2010. The profiles were made using a modified version of the method proposed by Emery (1961), already developed in Bustos et al. (2013). The analysis of the beach profiles was performed seasonally (summer, autumn, winter and spring). Additionally, others were surveyed after strong storms. The profiles were digitalized and the volumes for the sediment budget and the Annual Variation Rate (AVR) were calculated. The volume was calculated considering a constant beach width equal to 1 m and a length defined by the shorter profile. Principal Component Analysis (PCA) was applied to complete the analysis of the seasonal beach profiles. The study for all sectors demonstrated that du ring winter periods they all present concave profiles (Fig. 3), while during the summer periods were characterized by significant berms (Table 1). The profiles at ZC1 and ZC2 behaved rather similarly, whereas those at ZC3 were still more concave than the others. ZC3 during the winter of 2009 presented a 1.5 m microcliff on the dune front. Also, during the summer profiles showed areas of accumulation, mainly with the formation of berms and bars (Fig. 3). The sedimentary balance reflected the behavior of the profiles, with volume increment in the sum mer periods and reduction in winter (Fig. 4). ZC1 presented a negative balance with an erosional trend. ZC3 profiles had the highest losses, with up to 60 m3 of erosion in the winter of 2008. The TVA for both profiles were negative, for ZC1 it was 12.9 m3/ yr, and for ZC3 of 20.3 m3/yr. In contrast, ZC2 had a positive TVA (9.9 m3/yr). Its largest gain occurred in Autumn 2009 (65.6 m3) (Fig. 4). ZC3 showed more concave profiles than the rest and represents the place with higher sediment loss, especially during rainfall. The entrances to the beach are constructed perpendicularly to the coast and without vegetation protection. For this reason, they are easily eroded, mainly by rainwater runoff. Monthly characteristics and trends in the beha vior of the beach profiles were obtained by applying a PCA. The average profile of ZC1 presented a stable line with a slight concave tendency. Sediment loss was mainly observed in summer, winter and autumn; accretion occurred in spring (Fig. 5). The ZC2 profile showed a slightly concave shape, similar to ZC1, while small erosion cycles were observed every three months. The average profile showed losses in winter, spring and autumn, whereas it only gained sediment in summer (Fig. 6). The average profile in ZC3 is more concave than ZC1 and ZC2. The temporal components showed an erosion trend, with cycles of approximately six months of accretionerosion. During autumn, winter and spring the sediment of the average profile decreased while increased in the summer (Fig. 7). In order to evaluate the damages and response of the beach profiles to erosive events, the impact of a wind storm that occurred between 22 and 23 July is presented as an example. This event on the beaches of Pehuen Co was originated due to an extensive frontal storm. The winds associated with the front prevailed from the south with a maximum intensity of 63.7 km h1. The total length of the event was approximately 33 h. The waves on the beach, favored by the strong wind, reached 5 m in height (based on SMN map data). Beach profiles were made before and after the event to estimate volumetric differences. The effects on the beach and buildings were analyzed by field recognition after the event. Based on the profile data, we observed an erosive behavior with the profile becoming concave. ZC1 had a total volume loss of 3.17 m3, specifically on the backshore. The rest of the beach remained basically constant. The erosion caused damage to the infrastructures over the dune. In September (2009) the profile had recovered 2.38 m3 with respect to the prestorm profile. The ZC2 had a behavior similar to ZC1 in terms of sediment loss and gain. A volume of 9.16 m3 was lost. In September, a sediment recovery from the prestorm profile of 9.04 m3 was observed (Fig. 8). ZC3 had significant erosion in the dune area, with an escarpment of 1.6 m high. In this zone of the backshore, a volume loss of 6.51 m3 was recorded between the pre and poststorm profiles. In September, this profile did not recover as in the other two sites (ZC1 and ZC2). The escarpment began to diminish in height on December, four months after the storm occurred (Fig. 8). The ability to differentiate the behavior of the beach according to the coverage of its frontal dune is fundamental for landuse planning. Therefore, to find solutions applicable in the short and medium term is important to the natural balance, economic and social growth of these cities. It is concluded that in an erosive zone such as the central area of Pehuen Co, the frontal dune cover is decisive for coastal dynamics. The impact and recovery of the beach after storm events were better developed in places with vegetation cover over the dunes. In turn, the beach profiles in areas with perpendicular entrances to the beach had strong erosion processes and slow recovery. We recommend to modify the entrances to the beach and reduce their number as much as possible. Therefore, risk maps are needed in order to generate better planning for coastal urban development.